Kontekstualisasi Pemilihan Ayat dalam Tradisi Condong Tresno Studi Living Qur’an di Pondok Mambaul Falah - Rifqatul Husna; Aldona Novalika Rhomadhona (Kartika: Jurnal Studi Keislaman, 2026)
The concept of Living Qur'an examines how the Qur'an is internalized and practiced within the social life of Muslim communities. This study discusses the Condong Tresno tradition at Pondok Mambaul Falah Bondowoso, held regularly every 17th day of the Hijri month as a form of Living Qur'an through local culture. The activities include Qur'anic recitation, religious lectures (tausiyah), Javanese traditional attire, and gamelan music. Using a qualitative method with Sahiron Syamsuddin's perspective, this research aims to understand the meaning of Qur'anic recitation, its connection to the tausiyah theme, the spiritual impact on students, and community responses. The findings show that this tradition serves as cultural da'wah, integrating Islamic teachings with Javanese culture. The recited verses are thematically linked to the lecture topics, thereby strengthening students' religious understanding and spiritual experience. This tradition is not merely ceremonial but also shapes spirituality and religious values. The use of attributes such as blangkon, surjan, kebaya, and gamelan reflects the preservation of local culture for Islamic da'wah. Thus, the Condong Tresno tradition demonstrates that the Qur'an can live and thrive harmoniously within cultural practices and community social life